Disorders of the limbs. III. Hands and feet (continued). - Bonifazi, E.; Greco, I. (European Journal of Pediatric Dermatology, 2007)
Disorders of the limbs, particularly phytophotodermatosis, allergic dermatitis, autoimmune disorders of the skin, tumors and dermatitis artefacta are reported. Moreover, disorders of the nail in newborns and children are reported.